Structural Analysis of Single-Term Terminologies in Legal Texts - Tuvdendorj, Batbyamba (Mongolian Journal of Applied Linguistics, 2025)
Within the framework of the project titled “Lexical and Grammatical Study of Legal Language” conducted by the Department of Applied Linguistics at the Institute of Language and Literature, Mongolian Academy of Sciences, we created an electronic database consisting of 1,696,931 words from 449 laws currently in force in Mongolia. Based on this database, we aimed to present some results of our structural analysis of single-term legal terminologies. In our research, we relied on the core methodology of registering frequently used words in native language processing. We employed the “Attribute Description Method” to tag the materials in the database and combined this with manual annotation methods based on the “Mongolian Language Processing Demonstration Page (Laboratory, 2016).” Additionally, we utilized tools from AntConc and Excel programs to assess the usability of the lexicon, analyze word structures, and determine frequency of usage. We also made extensive use of various analytical methods such as summarizing, dissecting, and interpretive writing. When classifying terminologies from 1,399 sampled laws based on their formation, 219 were found to be of simple structure, while 1,180 were compound terms. According to word-formation methods in the Mongolian language, 140 of the terms were derived (neologisms), and 79 were non-derived terms. This structural analysis of single-term legal terminologies is important in determining whether the terms meet core terminological criteria—being concise, unambiguous, and accurate—as well as ensuring that the meanings and concepts of the constituent words align precisely. For Mongolia, such analysis serves as a foundational step toward understanding the structure, formation methods, and usage patterns of single-term terminologies in legal drafting, and ultimately contributes to the development of standardized legal terminology. Хуулийн бичвэр дэх дан нэр томьёоны бүтцийн судалгаа Хураангуй: Бид ШУА-ийн ХЗХ-ийн Хэрэглээний хэл шинжлэлийн салбарын “Хуулийн хэлний үгийн сан, хэл зүйн судалгаа” сэдэвт төсөлт ажлын хүрээнд Монгол Улсад хүчин төгөлдөр үйлчилж байгаа 449 хуулийн 1,696,931 үгтэй цахим санг байгуулав. Улмаар уг сандаа тулгуурлан хуулийн бичвэр дэх дан нэр томьёог бүтцийн талаас судалсан судалгааны зарим үр дүнгээ танилцуулахыг зорьсон болно. Бид судалгаандаа эх хэлний боловсруулалтад өргөн хэрэглэдэг үгсийг материалын санд бүртгэх үндсэн аргад түшиглэж,“Онцлогийг тодорхойлох арга” (Attribute Description Method)-аар материалын сандаа тэмдэг хадсан бөгөөд цахим сангийн боловсруулалтаа “Монгол хэл боловсруулалтын үзүүлэн хуудас (лаборатори, 2016)”-ыг гараар тэмдэглэгээ хийх аргатай хослуулсан. Түүнчлэн үгсийн сангийн хэрэглээний чанарыг үнэлэх, үгийн бүтэц, хэрэглээн дэх давтамжийг тогтооход АntConc болон EXCEL программын хэрэгслүүдийг ашигласнаас гадна нэгтгэн дүгнэх, задлан шинжлэх, тайлбарлан бичих зэрэг олон аргыг түлхүү ашиглав. Түүвэрлэн авсан 1399 хуулийн нэр томьёог бүтэх аргаар ангилж үзэхэд, дан бүтэцтэй нэр томьёо 219, нийлмэл бүтэцтэй нэр томьёо 1180 байна. Монгол хэлний үг бүтэх аргаар ангилж үзвэл, үүсмэл нэр томьёо 140, үүсмэл биш нэр томьёо 79 бүртгэгдэв. Энэхүү хуулийн дан нэр томьёоны бүтцийн судалгаа нь нэр томьёо товч тодорхой, салаа утгагүй бөгөөд оновчтой байхаас гадна нэр томьёог бүтээж байгаа үгийн утга, ухагдахуун нь хоорондоо яв цав тохирч байх ёстой гэсэн нэр томьёоны үндсэн шаардлагад нийцэж буй эсэхийг тодорхойлоход ач холбогдолтой юм. Монгол Улсын хувьд хуулийн хэл найруулгад ашиглаж буй дан нэр томьёоны бүтэц, бүтэх арга, хэрэглээний байдал, цаашлаад нэр томьёоны стандартыг бий болгоход шаардах эхний алхам нь уг төрлийн шинжилгээ болно. Түлхүүр үг: цахим сан, давтамж, нэр томьёо бүтэх арга, үгийн аймаг, нэр томьёоны орчуулга,